NETWORK TOPOLOGIES - Singh, Pankaj; Verma, Shubham (IJRDO -Journal of Computer Science Engineering, 2015)
The geometrical arrangement of computer resources, remote devices and communication facilities is known asNetwork structure or Network topology. A computer network is comprised of nodes and links, a node is the endpoint of any branch in a computer, a terminal device, workstation or interconnecting equipment facility. A link is acommunication path between two nodes. The terms “circuit” and “Channel” are frequently used as synonyms for thelink. There are different types of the topologies like bus, ring, tree, mesh etc.